PEMBERDAYAAN JAMU TRADISIONAL OMAH AMPIRAN WONOLOPO MELALUI PENGEMBANGAN PRODUK, BRANDING, DAN PEMASARAN DIGITAL - Nurchayati, Nurchayati; Imam Gozali,; Sukardi, Sukardi; Suparmi, Suparmi; Lisa Erfi Yunita, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Traditional jamu (herbal medicine) represents an invaluable part of Indonesian cultural heritage, yet it faces declining interest due to limited product innovation, weak branding, and minimal digital marketing adoption. This community service program aims to empower 25 traditional jamu entrepreneurs in Omah Ampiran Tourism Village, Wonolopo, Semarang City, through integrated product development, branding, and digital marketing. Using Participatory Action Research (PAR) over 24 weeks, the program completed its preparation phase (weeks 1-4) involving stakeholder engagement and need assessment. Baseline findings revealed that 84% have limited variants, 0% have registered trademarks, and 60% lack social media presence, with an average monthly revenue of IDR 2,450,000. The program includes three training clusters and intensive mentoring (weeks 5-20). Target outcomes: 80% developing three new variants, 90% establishing brand identity, 100% utilizing social media, and 70% registering on marketplaces. A sustainable community with peer-to-peer mentoring will ensure continuity, contributing to cultural heritage preservation and women's economic empowerment.